The government of Ucayali, Peru, adopts deforestation-free, low- emissions strategies to strengthen cocoa and palm oil value chains - Ivanova, Yovita (2022)
The strategies developed to promote deforestation-free, low- emission cocoa and oil palm value chains have been officially adopted by the regional government of Ucayali to guide public and private stakeholders towards improved sectorial and agricultural development. Both documents have been developed by the Alliance of Bioversity and CIAT in the framework of a project on “Business models to address drivers of deforestation in Peru” or Sustainable Amazon Businesses (SAB). Peru is implementing these sustainable business models in the agro-industry and livestock sectors to combat greenhouse gas emissions caused by deforestation. The aim is to enhance productivity in deforested areas and establish deforestation-free agricultural systems. These efforts align with Peru's climate goals in the Nationally Determined Contribution (NDC) and the Joint Declaration of Intent on REDD+.